ANALISIS KINERJA ANGGARAN REALISASI PENDAPATAN DAN BELANJA DAERAH (STUDI KASUS: KABUPATEN MALANG) - Sulistianto Ibrahim; Kumba Digdowiseiso (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. This study was made aimed at analyzing the Financial Performance of Regional Income in Malang City for the period 2017-2019 seen from income variance, income growth, spending efficiency analysis, financing analysis and shopping harmony analysis. The analysis used is the analysis of the analysis of expenditure variants, the analysis of expenditure growth, the ratio of expenditure efficiency, the analysis of financing, the analysis of the balance of expenditures and the ratio of operating and capital expenditures to the total. The data needed in this research is in the form of secondary data or archival research in which the data describes past events (historical). When viewed from the analysis of expenditure compatibility, Malang City Government still provides a large portion of operational expenditure compared to the portion for capital expenditure. The share of personnel spending is also quite large compared to capital expenditures. So that the Malang City Government in the plan and realization of regional expenditure is a greater portion of operational expenditure, while for public service support and economic support, such as infrastructure, irrigation and other assets including capital expenditures, it is still low.